2020
DOI: 10.31867/2523-4544/0121
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fertilizer systems on the formation of fertility of gray forest soil in short-rotational crop rotation under spring barley

Abstract: Наведено результати дослідження впливу систем удобрення і попередників на динаміку показників ефективної родючості сірого лісового ґрунту. Встановлено, що більший вміст польової та значніші запаси продуктивної вологи, а також посилене накопичення легкогідролізного азоту, рухомих форм фосфору й калію, нестабільних гумусових речовин (лабільного та водорозчинного гумусу) мають місце протягом вегетації ячменю ярого як в зерно-кормовій, так і плодозмінній сівозмінах у варіантах з інтенсивною органо-мінеральною сист… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was found that the accumulation of labile forms of humus was considerably influenced by precursors. Parallel studies of the authors conducted under a spring grain crop -barley, also confirmed differences in the accumulation of unstable humus compounds in the soil after winter wheat and potatoes (Kachmar et al, 2020). The influence of precursors (corn, barley, oats) on potato yield has been proven by Canadian scientists (N' Dayegamiye et al, 2017).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 72%
“…It was found that the accumulation of labile forms of humus was considerably influenced by precursors. Parallel studies of the authors conducted under a spring grain crop -barley, also confirmed differences in the accumulation of unstable humus compounds in the soil after winter wheat and potatoes (Kachmar et al, 2020). The influence of precursors (corn, barley, oats) on potato yield has been proven by Canadian scientists (N' Dayegamiye et al, 2017).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 72%
“…The duration of the period between harvesting the predecessor and sowing winter wheat is also important. Studies by Kachmar et al (2020) found that the larger it is, the deeper is the magnitude of the mineralisation processes of organic substances that have entered the soil environment and the immobilisation of the formed compounds into labile forms of humus (Table 1).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%